The Relationship Between Reactive Agility and Change of Direction Speed in Professional Female Basketball and Handball Players - Popowczak, Marek; Cichy, Ireneusz; Rokita, Andrzej; Domaradzki, Jarosław (Frontiers in Psychology, 2021)
Assessing players’ physical ability to make a change of direction (COD) and the cognitive-motor abilities revealed in reactive agility (RA) is necessary for understanding the physical requirements and capabilities of elite players in handball and basketball. The main aim of this study was to determine the differences between female professional basketball and handball players in COD, a reactive agility task. Moreover, the relationship between anthropometric features, agility, and parameters of perception was determined. Two scenarios of the Five-Time Shuttle Run to Gates test (planned and non-planned) were used to evaluate the COD speed and reactive agility. Significant differences were found in body height, the overall results of COD speed, and RA between female basketball and handball players (p < 0.05). The handball players did better in the two scenarios of the Five-Time Shuttle Run to Gates test. Most studies report significant simple correlations between anthropometric parameters, body height and body weight, and values for COD and reactive agility (r = 0.55–0.81). Moreover, after applying partial correlation significant relationships between reactive agility and reaction time or Reac-Index became apparent. This may indicate the need to take into account the other two variables in attempts to test RA. It is recommended to use partial correlations in subsequent studies because simple correlations are not reliable and may not reveal apparent relationships between the variables. Also, when determining the COD speed and RA, it is suggested to take into account anthropometric and perception variables, such as reaction time or REAC-INDEX.